HUBUNGAN KETEPATAN WAKTU KONSUMSI TABLET BESI DENGAN KEJADIAN ANEMIA PADA IBU HAMIL TM III DI WILAYAH KERJA PUSKESMAS PRINGSEWU LAMPUNG - Apri Sulistianingsih; Desi Ari Madiyanti (Viva Medika, 2017)
Iron deficiency anemia is the health problem in Indonesia, prevalence of anemia in pregnant still about 37,8%, this incident is still very high comparet from Malaysia and Singapore. Based on the result obtained for the pre survey in pringsewu anemia in pregnant women reach 44,4%. the purpose of this research, to determine the relationship the accuracy of an iron tablet consumption with incidence of anemia in Puskesmas Pringsewu. This type of research is carried out by analytic survey with cross sectional approach, sampling technique is random sampling. From sample that met the criteria obtained 95 pregnant women, from 95 pregnant woment 58 which taking iron tablet righ, and 37 not righ.and from 95 pregnant women the 67 people not experience anemia and the 28 people experience of anemia. Statistical test with chi square test obtained p value =0,000 less than Î±=0,005, The meaning there is determinan dringking accuracy relationship with incident anemia. With the value Odds Ratio = O.136.so, the prengnant women the right to comsume iron tablets have a risk 0,136 times smaller than the improrer taking iron tablet to anemic. The conclusion shows that pregnant women consume iron tablet has many appropriate as recommended by health professionals, thus for health workers counseling on iron tablets should still be submitted to the ANC pregnant women